2022
DOI: 10.1242/jeb.243734
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of directional information provided by unpolarised and polarised light in the heading direction network of the diurnal dung beetle Kheper lamarcki

Abstract: The sun is the most prominent source of directional information in the heading direction network of the diurnal, ball-rolling dung beetle Kheper lamarcki. If this celestial body is occluded from the beetle's field of view, the distribution of the relative weight between the directional cues that remain shifts in favour of the celestial pattern of polarised light. In this study, we continue to explore the interplay of the sun and polarisation pattern as directional cues in the heading direction network of K. la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
9
2
Order By: Relevance
“…In a recent study, Khaldy et al ( 2022 ) demonstrated Bayesian integration of celestial cues in dung beetle orientation. They tested Scarabaeus (Kheper) lamarcki in a controlled indoor arena and showed that the beetles could maintain directional orientation in their dung rolling behaviour with either a green light source that served as an artificial ersatz sun or with an artificial polarised light source.…”
Section: Maintaining Orientation Over Short Distancesmentioning
confidence: 99%
“…In a recent study, Khaldy et al ( 2022 ) demonstrated Bayesian integration of celestial cues in dung beetle orientation. They tested Scarabaeus (Kheper) lamarcki in a controlled indoor arena and showed that the beetles could maintain directional orientation in their dung rolling behaviour with either a green light source that served as an artificial ersatz sun or with an artificial polarised light source.…”
Section: Maintaining Orientation Over Short Distancesmentioning
confidence: 99%
“…Unfortunately, our current data do not allow us to answer this question, but it is possible that with the 365 + 530 nm combination, the excitation ratio fed into the colour opponent system was just right to facilitate antagonistic neural processing [11] and, as a consequence, the beetles relied more heavily on spectral directional information for orientation than in the other experimental conditions. Such flexible use of compass cue preferences relative to the prevailing visual scenery is well documented within the heading compass network of the beetles [40,41]. However, as soon as the intensity of the light presented in isolation was decreased by 1 log unit, the beetles could no longer orient to it (figure 4 b ), again demonstrating that intensity still plays a role when orienting with spectral information.…”
Section: Discussionmentioning
confidence: 86%
“…However, the influence of the polarizer became stronger with increased amounts of UV light transmitted. Celestial cue preferences in honeybees thus depend on the relative strengths of the two cues, 51 a finding that is also true in ants 36 and dung beetles 37 and is likely to be true for orientation cue preferences in bumblebees as well.…”
Section: Discussionmentioning
confidence: 88%
“…When orientation responses are examined in a natural environment or in a laboratory setting, some cues are weighted more heavily than others and therefore dominate in experimentally generated cue-conflict situations. 5,10,12,18,36,37 Since we demonstrated that B. terrestris will orient to overhead polarization patterns and a point source when both cues were in isolation, we next were interested in which of the two cues the bumblebees preferred to orient with when both were available in concert.…”
Section: Walking Bumblebees Use Simulated Celestial Cues For Orientationmentioning
confidence: 99%